Aktivitas Antioksidan dan Penghambat Xantin Oksidase dari Ekstrak Buah Andaliman (Zanthoxylum acanthopodium DC.) - Kristanty, Ruth Elenora; Mun'im, Abdul; Katrin, . (Jurnal Farmasi Indonesia, 2013)
The fruits of andaliman (Zanthoxylum acanthopodium DC.) are well known in North Sumatera and commonly used as seasoning for Batak traditional cuisine. Aims of this study were to determine the scavenging activity of free radicals and xanthine oxidase inhibitory activity from the andaliman fruit extracts after macerated garually in petroleum ether, dichloromethane, ethyl acetate, n-butanol, and methanol. Activity assay were evaluated in vitro by using DPPH and enzyme xanthine oxidase. The result showed that n-butanol extract has medium antioxidant activity with IC50 values of 53.51 μg/mL and methanol extract has strong antioxidant activity with IC50 values of 26.39 mg/mL. Xanthine oxidase inhibitory activity of the extract given by n-butanol and methanol are very strong with IC50 values of 3.69 μg/mL and 4.03 μg/mL. Keywords : antioxidant, free radical, xanthine oxidase, Zanthoxylum acanthopodium DC.